Transcriptome analysis of extended-spectrum β-lactamase-producing Escherichia coli and methicillin-resistant Staphylococcus aureus exposed to cefotaxime - Brochmann, P. R. (Sci Rep, 2018)
Previous studies on bacterial response to antibiotics mainly focused on susceptible strains. Here we characterized the transcriptional responses of distinct cephalosporin-resistant bacteria of public health relevance to cefotaxime (CTX), a cephalosporin widely used in clinical practice. Adaptation to therapeutic concentrations of CTX (30 µg/ml) was investigated by RNA sequencing in mid-exponential phase cultures of a methicillin-resistant Staphylococcus aureus (MRSA) and two genetically diverse E. coli producing CTX-M-15 or CMY-2 β-lactamase following genome sequencing and annotation for each strain. MRSA showed the most notable adaptive changes in the transcriptome after exposure to CTX, mainly associated with cell envelope functions. This reprogramming coincided with a transient reduction in cell growth, which also occurred in the CMY-2-producing E. coli but not in the CTX-M-15-producing strain. Re-establishment of growth in the CMY-2 producer proceeded without any notable adaptive transcriptional response, while limited reprogramming of gene transcription was observed in the CTX-M-15 producer. Our data show that the transcriptional response of CTX-resistant bacteria to CTX depends on the bacterial species, level of resistance and resistance determinant involved. Gene products induced in the presence of CTX may play an essential role for bacterial survival during therapy and merit further investigation as possible targets for potentiating CTX.